Peran Kelas Inspiratif Dalam Rangka Meningkatkan Kreativitas,Minat Dan Bakat Siswa Di SDN Se-Nagari Muaro Takung - Alimuddin, Alimuddin; Habib Bintang Anugrah; Indri Fauzizah; Salsabillah Nadea Putri; khoirunnisa Tj; Miza, Miza (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to describe the role of inspirational classes in developing students' creativity, interests, and talents in all elementary schools within Nagari Muaro Takung. This activity was initiated due to the limited opportunities for student expression outside of formal learning, particularly during school holidays. Using a qualitative case study approach, this research involved 308 students from four elementary schools who participated in training for dance, silat, and painting. Data were collected through participatory observation, documentation, and interviews with teachers, students, and local community members. The findings indicate that inspirational classes positively contribute to an increase in students' self-confidence, creativity, social skills, and discipline. Furthermore, these activities also foster an enjoyable and meaningful learning environment and encourage social recognition of students' potential. This initiative serves as an example of the implementation of non-academic education based on collaboration and cultural aspects. These findings reinforce the importance of continuously organizing similar programs at the elementary school level.